2016
DOI: 10.1088/2053-1583/3/2/025003
|View full text |Cite
|
Sign up to set email alerts
|

High pressure Raman study of layered Mo 0.5 W 0.5 S 2 ternary compound

Abstract: Ternary two-dimensional (2D) transition metal dichalcogenide compounds exhibit a tunable electronic structure allowing for control of the interlayer and the intralayer atomic displacement to efficiently tune their physical and electronic properties. Using a diamond anvil cell, hydrostatic pressure was applied to Mo 0.5 W 0.5 S 2 up to 40 GPa in order to study the optical phonon vibrational modes. Analysis of the high-pressure Raman spectra shows that the two in-plane E 2g modes resembling that of pristine MoS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…Two‐dimensional (2D) materials are considered to have a remarkable potential for applications in future electrical and optoelectronic devices. Of these materials, the semiconducting transition metal dichalcogenides (TMDs) are of particular interest for their tunable mechanical and electronic properties …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two‐dimensional (2D) materials are considered to have a remarkable potential for applications in future electrical and optoelectronic devices. Of these materials, the semiconducting transition metal dichalcogenides (TMDs) are of particular interest for their tunable mechanical and electronic properties …”
Section: Introductionmentioning
confidence: 99%
“…These ternary 2D compounds exhibit different electronic properties depending on their compositions . Within the bulk 2D alloy family, the most explored one is Mo x W (1 − x ) S 2 , for which the Raman scattering, piezoreflectence, reflectance, and scanning transmission electron microscopy have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The A 1 ′ mode originates from transverse vibration of Se−Se atoms and the E′ mode originates from longitudinal vibration of W−Se atoms in opposite directions; they correspond to the A 1g and E 1 2g modes in bulk WSe 2 , respectively . The LA(M) mode is the longitudinal acoustic phonon at the M symmetry point in the Brillouin zone, it is usually activated by lattice structural disorder …”
Section: Resultsmentioning
confidence: 99%
“…[22] The LA(M) mode is the longitudinal acousticp honon at the Ms ymmetry point in the Brillouin zone, [39,[42][43][44] it is usuallya ctivated by lattice structural disorder. [42][43][44][45][46][47][48][49] From the Raman spectra at 0t o3 1.37 GPa, shown in Figure 4, we can see the LA(M) ando ther second order vibrations give ar elatively weak intensity initially,b ut that as the pressure increases the intensity of the LA(M) mode clearly grows.A ll other main Raman peaks give ab roader width at high pressures;t hey are extracted by Lorentz profile function fittings and the pressure evolution of peak positions are summarized. We noticed that the E' vibration abates after the sample was sealed in DAC with pressure applied, and becomes broader after around1 0GPa.…”
Section: Resultsmentioning
confidence: 99%
“…nanosheet was performed by Akinwande and coworkers. [89] It was concluded that there are some new appearing peaks with the increasing of pressure to a certain GPa. For instance, a new peak at 470 cm -1 was only observed in the alloyed Mo0.5W0.5S2 nanosheet but not in the pristine MoS2 and WS2 nanosheet, which can be assigned to the disorder-activated outof-plane Raman mode resulted from the pressure.…”
Section: Ultrathin 2d Alloyed Metal Chalcogenide Nanosheetsmentioning
confidence: 99%